2005
DOI: 10.1111/j.1440-1746.2005.03796.x
|View full text |Cite
|
Sign up to set email alerts
|

Norfloxacin and cisapride combination decreases the incidence of spontaneous bacterial peritonitis in cirrhotic ascites

Abstract: Prophylaxis with norfloxacin and cisapride significantly reduces the incidence of SBP in high-risk cirrhosis patients; low serum albumin, low ascitic fluid protein and alcoholic cirrhosis predispose to the development of SBP in high-risk cirrhosis patients; and low ascitic fluid protein should also be considered as a risk factor for the development of SBP requiring prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Studies have shown that therapy with prokinetics, with or without antibiotics, in patients with cirrhosis leads to improved small bowel motility and reduced risk of SBP [34][35][36]. There are no studies so far on the role of prophylactic antibiotic therapy in cirrhotic patients with SIBO.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have shown that therapy with prokinetics, with or without antibiotics, in patients with cirrhosis leads to improved small bowel motility and reduced risk of SBP [34][35][36]. There are no studies so far on the role of prophylactic antibiotic therapy in cirrhotic patients with SIBO.…”
Section: Discussionmentioning
confidence: 96%
“…Although the reasons for prescription were not described in detail, these symptoms might be related to the use of gastric acid suppressants and/or prokinetic drugs. Previous studies have shown an association between gastrointestinal dysmotility and spontaneous bacterial peritonitis in patients with LC [13][14][15][16] . Therefore, we investigated the effects of prokinetics on PDrelated peritonitis, and our data showed that prokinetic use was not associated with a reduced risk of PD-related peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many patients with end-stage renal disease (ESRD) experience gastroparesis or reduced bowel movements, and several studies have identified an association between gastrointestinal dysmotility and spontaneous bacterial peritonitis in cirrhotic patients and animal models of liver cirrhosis (LC). Indeed, decreased intestinal motility and extended transit time can lead to bacterial overgrowth and bacterial translocation from the gastrointestinal tract [13][14][15][16] . However, no study has clarified the effects of prokinetics on PD-related peritonitis.…”
Section: Introductionmentioning
confidence: 99%
“…Selective intestinal decontamination with antibiotics reduces bacterial translocation [28] and decreases the risk of infections, especially those due to Gram negative bacteria [38,39]. Moreover, the addition of cisapride (a prokinetic agent) to norfloxacin has been reported to further decrease the incidence of SBP in cirrhotic patients with ascites [40]. This again supports the role of intestinal bacteria as a major infective source in cirrhotics and may explain why prophylactic antibiotics both orally and intravenously are so effective in reducing infections during variceal bleeding [41].…”
Section: Discussionmentioning
confidence: 97%